Law Enforcement against Criminal Acts of Motorcycle Gangs Criminal of Rumbing & Sharp Weapons - Johan Benbella Putra; Umar Ma'ruf (Law Development Journal, 2021)
The objectives of this study are as follows: To identify and analyze the factors that cause the gang attacks carried out by motorcycle gangs. To find out and analyzelaw enforcement against criminal offenses against motorbike gangs, perpetrators of beatings and sharp weapons.To find out and analyze obstacles and solutions in law enforcement against criminal offenses against motorbike gangs, perpetrators of beatings and sharp weapons.The approach to the problem that the writer uses in this legal research is included in juridical-empirical research, so what is examined initially is secondary data. This research is a descriptive research. Based on the results of this study, the factors that led to the gang attacking were carried out by motorcycle gangs, among others: a lack of understanding of the teenagers regarding the applicable provisions concerning the Traffic Law. Also caused as an influence on biological and psychological conditions. Biologically because they are in a period of growth and desire to show their existence to their peers and the environment. Law enforcement against criminal acts of beatings and carrying sharp weapons committed by motorcycle gang groups, namely by preventing and taking action. The obstacles are: The community, as a source of information about the occurrence of motorbike gangs, is afraid (skeptical) of the community about motorbike gangs, even though legal counseling has been carried out. The solution is: Coaching motorcycle gangs. Conducting legal education and prohibiting all acts of beating and carrying sharp weapons carried out by motorcycle gangs to the community.